Collaboration between startups and large firms: a new way to engage in open innovation - Kantis, Hugo (2023)
The acceleration of the technological progress forces corporations to review their innovation strategies, looking for a greater flexibility and faster knowledge acquisition to sustain their competitive advantages. In this context, collaboration with startups seems a plausible and effective way to pursuing open innovation strategies. Results show that collaborations between large firms and startups are a very recent though growing phenomenon but with a clear spatial concentration around the largest economies of the region. Its main motive refers to agile and flexible innovation, assuming multiple forms and activities. Interestingly, this phenomenon is neither restricted to certain technological industries nor to foreign-owned corporations. In addition, in-depth insights from case studies reveal some tensions and challenges at the corporate level to accommodate these collaborations with startups within the existing repertory of established routines and processes, as well as the importance of matching and aligning expectations between the corporation and the startups in terms of results and commitments. The cases showed the relevance of conceiving these collaborations as an entrepreneurial project itself within the organization and with a strong alignment with the parent company's strategy. Several future research avenues are derived from these results, aiming at nurturing this still emerging research field in Latin America.